Evaluating the influence of diet-related variables on breeding performance and home range behaviour of a top predator - Lourenço, Rui (2015)
Diet composition is linked to reproductive performance directly or indirectly by other life-history traits, including home range behaviour. The relationships between prey abundance, diet and individual fitness have often been explored. However, these relationships are complex and difficult to disentangle, especially in vertebrate top predators. Here, we present the results of a longterm study using multi-model inference procedures to elucidate the influence of diet-related variables on breeding parameters and home range behaviour of a top predator, the eagle owl Bubo bubo. Superpredation, diet diversity, rat biomass and rabbit mean weight were the most important variables when analysing reproductive parameters, suggesting that less diverse diets with greater rabbit biomass percentage may benefit reproductive performance, whereas rat biomass percentage is apparently associated with greater variation of breeding success. Earlier laying dates seem to be associated with the consumption, on average, of smaller rabbits. On the other hand, edge density was the most relevant factor determining the variation in home range behaviour, with individual characteristics, such as age and sex, also being important. Although the relative importance of the diet-related variables was generally low, mean weight of alternative prey, diet diversity and rabbit biomass also helped to explain home range parameters. In an optimal foraging context, centred on the abundance of the main prey species, our results suggest that when rabbits are less available eagle owls may increase home range size in order to obtain alternative prey, increasing at the same time their dietary diversity, which may also require higher movement speed.